PDMS-based ultraviolet curing 3D printing resin, 3D printing method and application
By adding appropriate components to the PDMS-based ultraviolet curing 3D printing resin, the efficiency and quality problems caused by high viscosity and slow curing speed in photocuring 3D printing are solved, and efficient and stable printing effects and precise control of complex structures are achieved.
Patent Information
- Application Number
- CN202411740309.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-25
AI Technical Summary
During the photocuring 3D printing process, PDMS has high viscosity and difficult flow resistance and interlayer adhesion, slow curing speed leads to low printing efficiency and unstable finished product quality, and poor compatibility affects the printing effect.
A PDMS-based ultraviolet curing 3D printing resin is used, which contains polyethylene glycol diacrylate, double-ended methacrylate-terminal polydimethylsiloxane, solvent, metal salt, crosslinking agent, photoinitiator and light absorber. Adjust the viscosity of PDMS by adjusting the type and amount of solvents, and selecting appropriate photoinitiators and light absorbers to optimize curing time and print quality.
It significantly improves the flowability and curing speed of PDMS in photocuring 3D printing, improves printing efficiency and finished product quality, solves compatibility problems, and realizes the printing of complex three-dimensional structures with accurate and controllable structure and flexible adjustment of porosity.
Smart Images

Figure CN119505511A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocuring 3D printing, and in particular to a PDMS-based ultraviolet light-curing 3D printing resin and a 3D printing method and application. Background Art
[0002] As an elastomer with stable physical and chemical properties, good biocompatibility and safety, and low cost, polydimethylsiloxane (PDMS) has been widely used in many fields such as medical devices, semiconductors, and electronics industries. Its unique thermal and chemical stability, flexibility, easy spreadability, hydrophobicity, and low glass transition temperature make it show great application potential in the battery field.
[0003] In the field of batteries, the specific applications of PDMS are mainly reflected in the following aspects: First, as an electrolyte additive, PDMS can optimize the performance of the electrolyte and significantly improve the cycle stability and Coulomb efficiency of the battery; secondly, by grafting on the surface of metal oxides to form an active layer, it can effectively inhibit the growth of lithium dendrites in lithium metal batteries, thereby enhancing the safety and cycle life of the battery; thirdly, PDMS macromolecules are "grafted" on the surface of lithium metal through electrochemical potential and electric field, which enhances the stability of the electrolyte interface, reduces internal side reactions, and further improves the safety performance of the battery; finally, cross-linking PDMS with polymer electrolytes can reduce the glass transition temperature of the polymer and improve the ionic conductivity and mechanical properties of the polymer electrolyte.
[0004] Researchers further discovered that PDMS exhibits good photocuring properties when cross-linked with other polymers, which provides new possibilities for the application of PDMS in the field of 3D printing. However, traditional PDMS 3D printing methods, such as the "molding-lighting" curing mode, which first uses a mold or DIW nozzle to extrude a fixed shape and then cures it by irradiating ultraviolet light, have problems such as long time consumption and a single shape of the prepared electrolyte, which makes it difficult to meet the manufacturing needs of complex three-dimensional structures with adjustable structures and controllable porosity.
[0005] Photocuring 3D printing technology has become an advanced manufacturing technology with its high precision, high efficiency, wide application range and smooth finished product surface. This technology uses ultraviolet light irradiation to trigger photocuring reaction to achieve rapid prototyping, which can significantly shorten the printing time of PDMS electrolyte, improve efficiency, and realize 3D printing of complex models with controllable structure and adjustable porosity according to actual application requirements. However, the application of PDMS in photocuring 3D printing also faces many challenges, such as the high viscosity of PDMS increases the flow resistance and interlayer adhesion difficulty during printing, the relatively slow curing speed of PDMS leads to low printing efficiency and unstable finished product quality, and the hydrophobicity of PDMS may affect its compatibility with other components in the printing ink.
[0006] Although there are patents that attempt to introduce PDMS nanoparticles as nanofillers into photosensitive resins to improve the lubricity and hydrophobicity of the material, this is only a preliminary exploration and has not deeply explored the potential of PDMS in UV-curable 3D printing resins. At present, there are still few resins that can achieve UV-curable 3D printing by forming a photocross-linked network between PDMS and other polymers. Therefore, the development of PDMS-based UV-curable 3D printing resins and their application in the field of battery electrolytes is expected to not only fill the market gap, but also promote the innovation and development of battery technology, and provide strong support for the commercial application of new battery systems.
[0007] However, how to optimize the formulation of photosensitive PDMS resin, especially the selection and ratio of photoinitiators and light absorbers, to optimize the performance of PDMS in the photocuring printing process is still a key technical problem that needs to be solved by technicians in this field. Through in-depth research on the photocuring mechanism of PDMS and the influencing factors in the printing process, it is expected that PDMS-based UV-curable 3D printing resins with better performance and stronger applicability will be developed, providing strong support for the further innovation and development of battery technology. Summary of the invention
[0008] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a PDMS-based UV-curable 3D printing resin to solve the problem that when PDMS is used in the process of photocuring 3D printing, the PDMS has high viscosity, large flow resistance and difficulty in interlayer adhesion during the printing process, which is not conducive to the molding of small and complex models, as well as the slow curing speed of PDMS, resulting in low printing efficiency and unstable finished product quality, and the poor compatibility of PDMS, which affects the printing effect.
[0009] Furthermore, a method for 3D printing using the above-mentioned PDMS-based UV-curable 3D printing resin is provided.
[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A PDMS-based ultraviolet light-curing 3D printing resin comprises the following components, measured by mass percentage: 35-55% of polyethylene glycol diacrylate, 5-15% of double-terminal methacrylate-terminated polydimethylsiloxane, 15-50% of a solvent, 0-30% of a metal salt, 2.5-10% of a cross-linking agent, 0.1-5% of a photoinitiator, and 0.01-3% of a light absorber.
[0011] Furthermore, the photoinitiator is at least one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide or 2,4,6-trimethylbenzoylethyl phosphate. The selection criteria of the photoinitiator are: (1) its absorption spectrum matches the emission spectrum of the ultraviolet light source, preferably the absorption peak is between 250 nm-500 nm, and more preferably matches the wavelength of the 3D printer ultraviolet light source such as 405 nm; (2) it maintains good solubility and dispersibility in the PDMS electrolyte system and does not cause system stratification or precipitation; (3) it has high photoinitiation efficiency and good thermal stability; the acylphosphine oxide photoinitiator selected in the present invention is a kind of free radical polymerization photoinitiator, and its absorption range is 380-450nm, which meets the selection criteria, and its unique molecular structure enables it to quickly absorb light energy under ultraviolet light irradiation and convert it into chemical energy, thereby initiating a polymerization reaction, effectively shortening the curing time, and improving printing efficiency and printing quality. In addition, the acylphosphine oxide photoinitiator has excellent solubility and dispersibility in the PDMS electrolyte system, and will not cause system stratification or precipitation. At the same time, it also has high photoinitiation efficiency and good thermal stability, which can meet the needs of high-precision processing technologies such as 3D printing. And the photoinitiator of the present invention has good compatibility with the battery system, and will not cause adverse reactions that affect battery performance.
[0012] Further, the light absorber is at least one of lemon yellow, Sudan I, methyl red or reactive orange 16. The selection of the light absorber is also crucial, which requires that the absorption wavelength can match the ultraviolet light source and the photoinitiator, and the ideal range is between 350-500 nm. This characteristic enables the light absorber to effectively capture the scattered light of the light source in the non-designed structure area, avoiding the curing of the non-designed structure and causing the printing accuracy to decrease. At the same time, the light absorber must also have good compatibility to ensure that the uniformity of the curing reaction and the overall performance of the material are not affected. In addition, good chemical stability and heat resistance are also indispensable characteristics of the light absorber to ensure its stability and reliability in various environments. The light absorber used in the present invention contains a benzene ring or an aromatic group, and its absorption wavelength range just covers 350-500 nm. The azo dye molecules in these light absorbers realize the transition of electrons inside the molecule through the conjugated system formed by the azo group and the connected aromatic group, so that they can absorb light of a specific wavelength. This unique design not only improves the light absorption efficiency, but also ensures the stable performance of the light absorber under the ultraviolet light source. More importantly, the light absorber of the present invention exhibits good compatibility with the battery system and does not cause adverse reactions, thereby ensuring the stability of battery performance. At the same time, its excellent chemical stability and heat resistance enable the light absorber to maintain stable performance in various complex environments, further improving the reliability and efficiency of high-precision processing technologies such as 3D printing.
[0013] Furthermore, the cross-linking agent is pentaerythritol tetrakis (3-mercaptopropionate).
[0014] Furthermore, the average molecular weight of the polyethylene glycol diacrylate is less than 1000. The higher the molecular weight, the greater the viscosity, which will have an adverse effect on printing, so the molecular weight is controlled to be less than 1000.
[0015] Furthermore, the metal salt is lithium, sodium, potassium, magnesium, zinc or aluminum salt.
[0016] Furthermore, the metal salt is at least one of LiPF6, LiTFSI, LiFSI, LiBF4, LiClO4, LiOTF, NaPF6, NaTFSI, NaFSI, NaBF4, NaClO4 or NaOTF.
[0017] Furthermore, the solvent is at least one of tetrahydrofuran, acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide or dimethyl sulfoxide.
[0018] A 3D printing method, using the above-mentioned PDMS-based UV-curable 3D printing resin for 3D printing, comprises the following steps: (1) Using 3D printing technology to print PDMS-based UV-curable 3D printing resin into a photocurable sample with a three-dimensional structure; (2) Wash and soak the light-cured sample to remove the residual resin in the sample; (3) Place the cleaned light-cured sample at 30-160°C and dry it at a constant temperature for 4-24 hours.
[0019] Application of the PDMS-based UV-curable 3D printing resin in batteries.
[0020] Working principle: The polyethylene glycol diacrylate and double-terminated methacrylate-terminated polydimethylsiloxane of the present invention both have modified functional groups that can achieve covalent bonding with a cross-linking agent through an efficient "thiol-click" chemical reaction, so that under the action of a photoinitiator, cross-linking polymerization of the polymer can be achieved. In addition, the present invention can adjust the viscosity of PDMS by controlling the type and amount of solvent added, thereby solving the problem that when PDMS is used in photocuring 3D printing, the high viscosity of PDMS causes high flow resistance and difficulty in interlayer adhesion during the printing process, which is not conducive to the molding of small and complex models; by regulating the type and amount of photoinitiator, the photocuring time can be effectively shortened, thereby improving printing efficiency and printing quality. At the same time, by regulating the type and amount of light absorber, the curing of non-designed structures can be avoided, thereby avoiding the decrease in printing accuracy caused by it. The synergistic effect of these three substances jointly promotes high-precision photocuring 3D printing of PDMS. Moreover, by adjusting the ratio of various substances such as photoinitiators and light absorbers, the present invention can obtain a complex three-dimensional structure with a precisely controllable structure and a flexible porosity during 3D printing, solving the problem of the difficulty in directly printing PDMS electrolytes with specific porosity and structural requirements in the past, and significantly improving the manufacturing efficiency and finished product quality. In addition, the light absorber and photoinitiator used in the present invention have good compatibility, solving the problem of poor compatibility of PDMS affecting the printing effect.
[0021] Compared with the prior art, the present invention has the following beneficial effects: 1. The PDMS-based UV-curable 3D printing resin provided by the present invention can adjust the viscosity of PDMS by controlling the type and amount of solvent added, thereby solving the problem that when PDMS is used in the process of photocuring 3D printing, the flow resistance and interlayer adhesion difficulty of the printing process are high due to the high viscosity of PDMS, which is not conducive to the molding of small and complex models; by regulating the type, amount and ratio of the photoinitiator and the light absorber, the light curing time can be effectively shortened, thereby improving the printing efficiency and printing quality, while avoiding the curing of non-designed structures, resulting in a decrease in printing accuracy. In addition, the light absorber and the photoinitiator used in the present invention have good compatibility, which solves the problem that the compatibility of PDMS is poor and affects the printing effect.
[0022] 2. 3D printing using the PDMS-based UV-curable 3D printing resin prepared by the present invention can obtain a complex three-dimensional structure with a precisely controllable structure and flexibly adjustable porosity, and has high printing and curing efficiency, high layer resolution, clear structure, and complete through-holes, which solves the previous problem of being difficult to directly print PDMS electrolytes with specific porosity and structural requirements, and significantly improves manufacturing efficiency and finished product quality.
[0023] 3. The materials obtained by 3D printing using the PDMS-based UV-curable 3D printing resin of the present invention can be used in the field of batteries. By precisely controlling the shape, structure and porosity of the 3D structure, the transmission path of ions can be optimized, and the charging and discharging efficiency and cycle stability of the battery can be improved. At the same time, the excellent properties of PDMS, such as good thermal stability and chemical stability, can be used to further improve the safety and electrochemical properties of the battery. In addition, by finely controlling the printing formula and post-processing conditions, PDMS materials with different physical properties can be produced to adapt to the wide application of multiple battery systems such as lithium / sodium / potassium / magnesium / zinc / aluminum ion batteries, providing strong support for the innovation and development of battery technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The configuration and printing flow chart of the PDMS-based UV-curable 3D printing resin of the present invention; Figure 2 The 3D printed object images and SEM images thereof obtained by three printings of Example 1 of the present invention, wherein (a), (b), and (c) correspond to the 3D printed object images of the first printing, the second printing, and the third printing, respectively; (d), (e), and (f) correspond to the SEM images of the 3D printed object of the first printing, the second printing, and the third printing, respectively (scale bar is 100 μm); Figure 3 The complex three-dimensional structure model diagram designed for the present invention, (a), (b), (c) correspond to the front view, right view and top view of the square lattice structure respectively; (d), (e), (f) correspond to the front view, right view and top view of the diamond lattice structure respectively; (g), (h), (i) are the front view, right view and top view of the gyroid three-period minimum surface structure. DETAILED DESCRIPTION
[0025] The specific implementation modes of the present invention are further described in detail below in conjunction with specific examples.
[0026] The numerical ranges in the present invention are understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Each smaller range between any intermediate value in the stated value or stated range and any other stated value or intermediate value in the stated range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the range.
[0027] Unless otherwise stated, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art described in the present invention are generally understood. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of conflict with any incorporated document, the content of this specification shall prevail. Regarding "comprising", "including", "having", "containing", etc. used herein, they are all open terms, which means including but not limited to.
[0028] Unless otherwise specified, the experimental methods used in the present invention are all conventional methods.
[0029] Unless otherwise specified, the materials, reagents, etc. used in the present invention can be purchased or synthesized by known methods.
[0030] The quantitative tests in the present invention were all repeated three times, and the results were averaged.
[0031] Example 1 This embodiment provides a PDMS-based UV-curable 3D printing resin, and the preparation steps include: (1) 28.4 g of polyethylene glycol diacrylate, 7.8 g of dual-terminal methacrylate-terminated polydimethylsiloxane, 26.5 g of N,N-dimethylformamide and 6.32 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were mixed in a glass bottle and stirred for 12 h in a dark environment to obtain a PDMS polymer precursor solution; (2) Then, 2 g of pentaerythritol tetrakis(3-mercaptopropionate) and 712 mg of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819) were added to the PDMS polymer precursor solution and stirred for 12 h in a darkened state. Finally, 22.4 mg of tartrate was added and stirred for 12 h in a darkened state to obtain a PDMS-based UV-curable 3D printing resin.
[0032] Resin curing test: The above resin is kept in a dark place for 12 hours, and then the obtained solution is dropped onto a circular piece, and irradiated with a 405nm ultraviolet lamp to measure its curing time.
[0033] 3D printing experiment: Printing equipment: LCD 3D printer (Saturn 4 Ultra).
[0034] Before each print, measure the curing time of the resin, then take the resin for printing.
[0035] First print: Curing time was 11 s. Print a square lattice structure with a unit cell size of 0.4*0.4*0.4 mm and an overall size of 32*32*0.6 mm. Four pieces were printed at the same time. The printing exposure time was set to 11 s and the bottom layer exposure time was 172 s. One piece was incomplete due to insufficient solution.
[0036] Second printing: curing time is 9 s; set the printing exposure time to 8.8 s, the bottom layer exposure time to 150 s, and print a diamond lattice structure with a cell size of 0.8*0.8*0.6mm, a wall thickness of 100μm, a pore diameter of 220μm, and an overall size of 32*32*0.6mm.
[0037] The third print: the curing time is 6s; the printing exposure time is set to 5.5s, the bottom layer exposure time is 105s, the printing size is 32*32*0.6mm, the surface thickness is 100μm, the unit cell is 1*1*0.6mm, and the slice thickness is 0.05mm. The curved hole three-periodic minimum surface (TPMS) gyroid structure.
[0038] Post-processing: The model after three prints was immersed in an ethanol solution, and then placed in an ultrasonic cleaner for cleaning for 0.5-1 h, and then replaced with clean ethanol for 5-6 h, and then replaced with ethanol solution for soaking overnight, and washed several times until the ethanol solution after soaking no longer changed color. The model was then placed in a vacuum drying oven at 60 ° C for 24 h. At this time, all printed structures were through-hole structures. After drying, it was cut into 16 mm diameter discs using a cutting machine.
[0039] The configuration and printing flow chart of the PDMS-based UV-curable 3D printing resin of the present invention are as follows: Figure 1 shown.
[0040] The 3D printed object and its SEM image obtained by three printings in this embodiment are as follows Figure 2 As shown, (a), (b), and (c) correspond to the 3D printed objects of the first printing, the second printing, and the third printing, respectively; (d), (e), and (f) correspond to the SEM images of the 3D printed objects of the first printing, the second printing, and the third printing, respectively (the scale bar is 100 μm); Figure 2The subtle and complex structures printed by 3D printing can be clearly observed, and the printed structure is clear and fully through-hole.
[0041] Figure 3 In the figure, (a), (b), and (c) correspond to the front view, right view, and top view of the square lattice structure, respectively; (d), (e), and (f) correspond to the front view, right view, and top view of the diamond lattice structure, respectively; (g), (h), and (i) are the front view, right view, and top view of the gyroid three-period minimum surface structure. Figure 3 For complex structure 3D design drawings, that is, the expected effect of the printing result, Figure 2 Comparing the printed object with the SEM image, it can be seen that the designed complex structure can be clearly printed.
[0042] Example 2 This embodiment provides a PDMS-based UV-curable 3D printing resin, and the preparation steps include: (1) 21.3 g of polyethylene glycol diacrylate, 5.9 g of dual-terminal methacrylate-terminated polydimethylsiloxane, 20 g of tetrahydrofuran and 4.74 g of lithium hexafluorophosphate (LiPF6) were mixed in a glass bottle and stirred for 12 h in a dark environment to obtain a PDMS polymer precursor solution; (2) Then, 1.5 g of pentaerythritol tetrakis(3-mercaptopropionate) and 534 mg of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819) were added to the PDMS polymer precursor solution, and the mixture was stirred for 6 h in a darkened state. Finally, 53.4 mg of Sudan I (Sudan Red No. 1) was added, and the mixture was stirred for 6 h in a darkened state to obtain a PDMS-based UV-curable 3D printing resin.
[0043] Resin curing test: The above resin is kept in a dark place for 12 hours, and then the obtained solution is dropped onto a circular piece, and irradiated with a 405nm ultraviolet lamp to measure its curing time.
[0044] 3D printing experiment: Printing equipment: LCD 3D printer (Saturn 4 Ultra).
[0045] Before each print, measure the curing time of the resin, then take the resin for printing.
[0046] First print: curing time 17s, print size 32*32*0.6 mm diamond lattice structure, with wall thickness 100 μm, pore diameter 220 μm, four pieces printed at the same time, set print exposure time to 17.6 s, bottom layer exposure time to 280 s, exposure time is slightly insufficient.
[0047] Second printing: The curing time was 17 s, the printing exposure time was set to 18 s, the bottom layer was exposed for 280 s, the printing wall thickness was 100 μm, the pore diameter was 250 μm, and the overall size was a square lattice structure of 32*32*0.6 mm.
[0048] The third print: The curing time is 9 s. The print exposure time is set to 8.8 s, the bottom layer exposure time is 145 s, the print cell size is 0.4*0.4*0.4 mm, and the overall size is a square lattice structure of 32*32*0.6 mm.
[0049] Fourth print: curing time is 7 s. Set the print exposure time to 6.8 s, the bottom exposure time to 120 s, the print size to 32*32*0.6 mm, the surface thickness to 100 μm, the unit cell to 1*1*0.6 mm, and the slice thickness to 0.05 mm for a curved hole three-periodic minimum surface (TPMS) gyroid structure.
[0050] Post-processing: The successfully printed model was immersed in an ethanol solution, and then placed in an ultrasonic cleaner for 0.5-1 h, and then immersed in an ethanol bath for multiple times until the ethanol solution no longer changed color after the last immersion. The printed diaphragm structure was taken out, and the diaphragm was orange-yellow. The model was then placed in a vacuum drying oven at 60 °C for 6 h. At this time, all the printed structures were clear and all were through-hole structures.
[0051] Example 3 This embodiment provides a PDMS-based UV-curable 3D printing resin, and the preparation steps include: (1) 21.3 g of polyethylene glycol diacrylate, 5.9 g of dual-terminal methacrylate-terminated polydimethylsiloxane, 19.9 g of dimethyl sulfoxide and 4.74 g of lithium trifluoromethanesulfonate (LiOTF) were mixed in a glass bottle and stirred for 12 h in a dark environment to obtain a PDMS polymer precursor solution; (2) Then, 1.8 g of pentaerythritol tetrakis(3-mercaptopropionate), 400 mg of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, and 16.2 mg of methyl red were added to the PDMS polymer precursor solution and stirred for 6 h under light shielding to obtain a PDMS-based UV-curable 3D printing resin.
[0052] Resin curing test: The above resin is kept shading from light for 1 hour and then placed still. Then the obtained solution is dropped onto a circular piece and irradiated with a 405nm ultraviolet lamp to measure its curing time.
[0053] 3D printing experiment: Printing equipment: LCD 3D printer (Saturn 4 Ultra).
[0054] Before each print, measure the curing time of the resin, then take the resin for printing.
[0055] First print: The curing time was 16s, the print size was a circular straight through hole lattice structure with a diameter of 10 mm and a thickness of 0.6 mm. The lattice unit was 0.8*0.8*0.3 mm, the wall thickness was 100 μm, the pore diameter was about 200 μm, and the print structure was complete with clear and complete through holes.
[0056] Second printing: curing time was 15s, printing size was 10 mm in diameter, 0.6 mm thick curved hole three-period minimum surface (TPMS) gyroid structure, surface thickness was 100 μm, unit cell was 0.8*0.8*0.6 mm, slice layer thickness was 0.05 mm, exposure time was 15.3 s, bottom layer exposure time was 210 s, surface texture was clear, printing accuracy in the z-axis direction was not high, and some holes in the middle of the z-axis were blocked.
[0057] Example 4 This embodiment provides a PDMS-based UV-curable 3D printing resin, and the preparation steps include: (1) 17.76 g of polyethylene glycol diacrylate, 5 g of dual-terminal methacrylate-terminated polydimethylsiloxane, 17 g of acetonitrile and 3.95 g of sodium bis(trifluoromethylsulfonyl)imide (NaTFSI) were mixed in a glass bottle and stirred for 12 h in a dark environment to obtain a PDMS polymer precursor solution; (2) Then, 1.2 g of pentaerythritol tetrakis(3-mercaptopropionate), 445 mg of 2,4,6-trimethylbenzoylethyl phosphate, and 14 mg of reactive orange 16 were added to the PDMS polymer precursor solution and stirred for 12 h under light shielding to obtain a PDMS-based UV-curable 3D printing resin.
[0058] Resin curing test: The above resin is kept shading from light for 2 hours and then placed still. Then the obtained solution is dropped onto a circular piece and irradiated with a 405nm ultraviolet lamp to measure its curing time.
[0059] 3D printing experiment: Printing equipment: LCD 3D printer (Saturn 4 Ultra).
[0060] Before each print, measure the curing time of the resin, then take the resin for printing.
[0061] First print: curing time is 13-14 s. Print size is 10 mm in diameter, 0.6 mm thick curved hole three-period minimum surface (TPMS) gyroid structure, surface thickness is 100 μm, unit cell is 1*1*0.6 mm, slice thickness is 0.05 mm, exposure time is 12.8 s, and bottom exposure time is 200 s. After printing, soak it in ethanol solution for half an hour, take it out and observe the texture clearly.
[0062] Second printing: curing time is 9-10 s, setting the printing exposure time to 9.7 s, the bottom layer exposure time to 160 s, and printing a curved hole three-period minimum surface (TPMS) gyroid structure with a size of 32*32*0.6 mm, a surface thickness of 100 μm, a unit cell of 1*1*0.6 mm, a slice layer thickness of 0.05 mm, an exposure time of 9.7 s, and a bottom layer exposure time of 160 s.
[0063] The printed model was immersed in an ethanol solution, then placed in an ultrasonic cleaner for half an hour, and then replaced with clean ethanol to soak for 5-6 hours, and then replaced with an ethanol solution to soak overnight. The 3D printed structure was observed to be slightly yellowish at this time. The model was divided into two halves, one half was dried in the air, and the other half was dried in a blast drying oven at 160°C for 12 hours. By comparison, it was found that the dried half had a clearer structure and a smoother surface. It can be seen that constant temperature drying has a better treatment effect than direct drying in the air.
[0064] Example 5 This embodiment provides a PDMS-based UV-curable 3D printing resin, and the preparation steps include: (1) 3.55 g of polyethylene glycol diacrylate, 0.5 g of dual-terminal methacrylate-terminated polydimethylsiloxane, 3.3 g of N-methylpyrrolidone and 0.5 g of sodium trifluoromethanesulfonate (NaOTF) were mixed in a glass bottle and stirred for 12 h in a dark place to obtain a PDMS polymer precursor solution; (2) Then, 0.26 g of pentaerythritol tetrakis(3-mercaptopropionate) and 31.5 mg of photoinitiator 819 were added to the PDMS polymer precursor solution and stirred for 6 h in a light-shielded manner. Then, 4.6 mg of Sudan I was added and stirred for 6 h in a light-shielded manner to obtain a PDMS-based UV-curable 3D printing resin.
[0065] The above resin was kept shielded from light and left to stand for 12 h. Then, the obtained solution was dropped onto a circular piece and irradiated with a 405 nm ultraviolet lamp. The curing time was measured to be 12 s.
[0066] Example 6 This embodiment provides a PDMS-based UV-curable 3D printing resin, and the preparation steps include: (1) 31.9 g of polyethylene glycol diacrylate, 7 g of dual-terminal methacrylate-terminated polydimethylsiloxane, 20 g of tetrahydrofuran and 7.11 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were mixed in a glass vial and stirred overnight in a dark place to obtain a PDMS polymer precursor solution; (2) Then, 4.5 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 2.5 g of photoinitiator 819 were added to the PDMS polymer precursor solution and stirred for 2 h. Then, 300 mg of Sudan I was added and stirred for 6 h under light-shielding conditions to obtain a PDMS-based UV-curable 3D printing resin.
[0067] Take the above resin, use a UV lamp with a wavelength of 405 nm, and drop a disc to measure its curing time of 10 s. Take the above resin and use an LCD 3D printer (Saturn 4 Ultra) to print a straight through hole lattice structure with a size of 10*10*0.6 mm, a lattice unit of 0.8*0.8*0.3 mm, a wall thickness of 100 μm, and a hole diameter of 200 μm. The printed structure is clear and completely through-hole.
[0068] Example 7 This embodiment provides a PDMS-based UV-curable 3D printing resin, and the preparation steps include: (1) 14.2 g of polyethylene glycol diacrylate, 3.6 g of dual-terminal methacrylate-terminated polydimethylsiloxane, 13.2 g of N,N-dimethylformamide and 3.16 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were mixed in a glass bottle and stirred for 12 h in a dark environment to obtain a PDMS polymer precursor solution; (2) Then, 1 g of pentaerythritol tetrakis(3-mercaptopropionate) and 356 mg of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819) were added to the PDMS polymer precursor solution, and the mixture was stirred for 12 h under shade. Finally, 23 mg of methyl red was added and stirred for 6 h under shade to obtain a PDMS-based UV-curable 3D printing resin.
[0069] Take the above resin, use a UV lamp with a wavelength of 405 nm, and drop a disc to measure its curing time of 8 s. Take the above resin and use an LCD 3D printer (Saturn 4 Ultra) to print a square straight through hole lattice structure with a size of 10*10*0.6 mm, a lattice unit of 0.8*0.8*0.3 mm, a wall thickness of 100 μm, and a hole diameter of 200 μm. The printed structure is clear and completely through-hole.
[0070] Comparative Example 1 This comparative example provides a PDMS-based UV-curable 3D printing resin, and its preparation steps are mainly the same as those in Example 6, except that benzoin dimethyl ether is used to replace the photoinitiator 819.
[0071] Take the above resin, use a UV lamp with a wavelength of 405 nm, and drop a disc to measure its curing time of 60 s. Take the above resin and use an LCD 3D printer (Saturn 4 Ultra) to print a through-hole lattice structure with a size of 10*10*0.6 mm, a lattice unit of 0.8*0.8*0.3 mm, a wall thickness of 100 μm, and a pore diameter of 200 μm. The curing time needs to be further shortened, and the clarity of the 3D printed structure needs to be further improved.
[0072] By comparing Example 6 with Comparative Example 1, it can be found that, compared with the photoinitiator dimethyl benzoate, the photoinitiator 819 of the present invention has better printing effect of initiating curing and a shorter curing time, which can improve printing efficiency and printing quality.
[0073] Comparative Example 2 This comparative example provides a PDMS-based UV-curable 3D printing resin, and its preparation steps are mainly the same as those in Example 7, except that the light absorber methyl red is not added in this comparative example.
[0074] Take the above resin, use an ultraviolet lamp with a wavelength of 405 nm, and drop a disc to measure its curing time of 5 s. Take the above resin and use an LCD 3D printer (Saturn 4 Ultra) to print a square straight through hole lattice structure with a size of 10*10*0.6 mm, a lattice unit of 0.8*0.8*0.3 mm, a wall thickness of 100 μm, and a hole diameter of 200 μm. The printed sample shows that the structure is not printed clearly, and local curing occurs in the hole part (there is curing around the printed structure wall or beam, resulting in local curing of the hole, and no longer showing the clear through hole in Figure 2, and the accuracy and clarity of the structure are not high), resulting in low printing accuracy.
[0075] By comparing Example 7 with Comparative Example 2, it can be seen that a light absorber needs to be introduced to improve printing accuracy.
[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.
Claims
1. A PDMS-based UV-curable 3D printing resin, characterized in that: Calculated by mass percentage, the composition includes: 35-55% of polyethylene glycol diacrylate, 5-15% of double-terminal methacrylate-terminated polydimethylsiloxane, 15-50% of solvent, 0-30% of metal salt, 2.5-10% of crosslinking agent, 0.1-5% of photoinitiator and 0.01-3% of light absorber.
2. The PDMS-based UV-curable 3D printing resin according to claim 1, characterized in that: The photoinitiator is at least one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide or 2,4,6-trimethylbenzoylethyl phosphate.
3. The PDMS-based UV-curable 3D printing resin according to claim 1, characterized in that: The light absorber is at least one of lemon yellow, Sudan I, methyl red or reactive orange 16.
4. The PDMS-based UV-curable 3D printing resin according to claim 1, characterized in that: The cross-linking agent is pentaerythritol tetrakis (3-mercaptopropionate).
5. The PDMS-based UV-curable 3D printing resin according to claim 1, characterized in that: The average molecular weight of the polyethylene glycol diacrylate is less than 1000.
6. The PDMS-based UV-curable 3D printing resin according to claim 1, characterized in that: The metal salt is at least one of LiPF6, LiTFSI, LiFSI, LiBF4, LiClO4, LiOTF, NaPF6, NaTFSI, NaFSI, NaBF4, NaClO4 or NaOTF.
7. The PDMS-based UV-curable 3D printing resin according to claim 1, characterized in that: The solvent is at least one of tetrahydrofuran, acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide or dimethyl sulfoxide.
8. A 3D printing method, characterized in that: Using the PDMS-based UV-curable 3D printing resin according to any one of claims 1 to 7 for 3D printing, comprising the following steps: (1) Using 3D printing technology to print PDMS-based UV-curable 3D printing resin into a photocurable sample with a three-dimensional structure; (2) Wash and soak the light-cured sample to remove the residual resin in the sample; (3) Place the cleaned light-cured sample at 30-160°C and dry it at a constant temperature for 4-24 hours.
9. Application of the PDMS-based UV-curable 3D printing resin according to any one of claims 1 to 7 in batteries.